A quantum dot single spin meter - Wabnig, J; Lovett, B (IOP Publishing, 2009)
We present the theory of a single spin meter consisting of a quantum dot in a magnetic field under microwave irradiation combined with a charge counter. We show that when a current is passed through the dot, a change in the average occupation number occurs if the microwaves are resonant with the on-dot Zeeman splitting. The width of the resonant change is given by the microwave-induced Rabi frequency, making the quantum dot a sensitive probe of the local magnetic field and enabling the detection of the state of a nearby spin. If the dot-spin and the nearby spin have different g-factors, a non-demolition readout of the spin state can be achieved. The conditions for a reliable spin readout are found.